Pleurisy - Udoh, Andikan Effiong; Demydenko, Ganna (My University, 2015)
Pleurisy is a condition in which the pleura — a membrane consisting of a layer of tissue that lines the inner side of the chest cavity and a layer of tissue that surrounds the lungs — becomes inflamed. Also called pleuritis, pleurisy causes sharp chest pain (pleuritic pain) that worsens during breathing.
Keywords: pleurisy